The relationship between the effect of panic attack and physiological parameters in some patients and animals lab - Sara Maziad Ali; Mohammad Khalil (Tikrit Journal of Pure Science, 2024)
The effects of a panic attack were studied in some patients who do not have hereditary diseases "sudden onset" as well as using laboratory animal "rats" to examine the types of effects on some physiological parameters. compared with control. These attacks affect daily life and result from a complex interaction between environmental, neurological, and psychological factors. Venous blood samples were collected from people suffering from non-genetic diseases. Blood samples were also collected from experimental animals exposed to fear at intervals of 0, 3, 7, and 28 days to detect the relationship between environmental factors and some physiological factors. Statistical analysis was performed using the SPSS program. The results indicated an increase in the level of cholesterol, glucose, and C-reactive protein in people with non-genetic diseases compared to their decrease in the control group, in addition to an increase in the level of cholesterol and glucose and no effect on C-reactive protein in rats exposed to the impact of fear and low body weight. The results also show a significant increase in heart and breathing rates and a significant decrease in oxygen levels.